Castleman disease – clinical case report - Mendonça, Catarina (2008)
Castleman’s disease (CD) is an atypical lymphoproliferative disease that affects B cells and in which we can distinguish 3 variants. Its approach is different according to the presenting form: solitary or multicentric.The authors present a clinical case of multicentric CD, plasma cell variant, in a patient not infected by human immunodeficiency virus. Based on the case, the authors make a revision of the literature concerning this disease.